Multimodal treatment with curative intent in a germline BRCA2 mutant metastatic ampullary adenocarcinoma: a case report - Gianluca Mauri; Viviana Gori; Giorgio Patelli; Laura Roazzi; Francesco Rizzetto; Luciano De Carlis; Anna Mariani; Ugo Cavallari; Elisabetta Prada; Tiziana Cipani; Maria Costanza Aquilano; Emanuela Bonoldi; et al. (World Journal of Surgical Oncology, 2023)
Abstract Background Cancers of the Vater ampulla (ampullary cancers, ACs) account for less than 1% of all gastrointestinal tumors. ACs are usually diagnosed at advanced stage, with poor prognosis and limited therapeutic options. BRCA2 mutations are identified in up to 14% of ACs and, differently from other tumor types, therapeutic implications remain to be defined. Here, we report a clinical case of a metastatic AC patient in which the identification of a BRCA2 germline mutation drove a personalized multimodal approach with curative-intent. Case presentation A 42-year-old woman diagnosed with stage IV BRCA2 germline mutant AC underwent platinum-based first line treatment achieving major tumor response but also life-threatening toxicity. Based on this, as well as on molecular findings and expected low impact of available systemic treatment options, the patient underwent radical complete surgical resection of both primary tumor and metastatic lesions. Following an isolated retroperitoneal nodal recurrence, given the expected enhanced sensitivity to radiotherapy in BRCA2 mutant cancers, the patient underwent imaging-guided radiotherapy leading to long-lasting complete tumor remission. After more than 2 years, the disease remains radiologically and biochemically undetectable. The patient accessed a dedicated screening program for BRCA2 germline mutation carriers and underwent prophylactic bilateral oophorectomy. Conclusions Even considering the intrinsic limitations of a single clinical report, we suggest that the finding of BRCA germline mutations in ACs should be taken into consideration, together with other clinical variables, given their potential association with remarkable response to cytotoxic chemotherapy that might be burdened with enhanced toxicity. Accordingly, BRCA1/2 mutations might offer the opportunity of personalizing treatment beyond PARP inhibitors up to the choice of a multimodal approach with curative-intent.